2021
DOI: 10.3390/f12121668
|View full text |Cite
|
Sign up to set email alerts
|

Response of Spatio-Temporal Differentiation Characteristics of Habitat Quality to Land Surface Temperature in a Fast Urbanized City

Abstract: The degradation and loss of global urban habitat and biodiversity have been extensively studied as a global issue. Urban heat islands caused by abnormal land surface temperature (LST) have been shown to be the main reason for this problem. With the accelerated urbanization process and the increasing possibility of abnormal temperatures in Zhengzhou, China, more and more creatures cannot adapt and survive in urban habitats, including humans; therefore, Zhengzhou was selected as the study area. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…The value range was 0-1, with values close to 1 meaning higher habitat quality, and those closer to 0, meaning lower habitat quality. We followed the recommended values in the InVEST model manual and relevant literature and set the model parameters in combination with the actual situation of the study area [11,[49][50][51]. The main calculation formulas are as follows:…”
Section: Habitat Quality Calculationmentioning
confidence: 99%
“…The value range was 0-1, with values close to 1 meaning higher habitat quality, and those closer to 0, meaning lower habitat quality. We followed the recommended values in the InVEST model manual and relevant literature and set the model parameters in combination with the actual situation of the study area [11,[49][50][51]. The main calculation formulas are as follows:…”
Section: Habitat Quality Calculationmentioning
confidence: 99%
“…At present, scholars at home and abroad have mainly focused on assessing and predicting regional habitats [24][25][26] and exploring spatial and temporal variation characteristics [25], spatial and temporal evolution characteristics [27], relationships with ecological responses [26], and the construction of evaluation systems [28]. However, few studies have been conducted on the mechanisms that influence spatial variation in habitat quality.…”
Section: Introductionmentioning
confidence: 99%
“…The supposed scarcity of the species in northwestern Syria could be attributed to the shortage of suitable surface water. Review of the research literature showed that there are few studies on the relationship between habitat suitability and connectivity, and LST analysis has been carried out on small scales such as at the city [ 44 ] or at the wetland scales [ 45 ]. The present study aims to investigate the impact of increasing and decreasing trends of LST on habitat suitability and connectivity.…”
Section: Introductionmentioning
confidence: 99%